Numerical analysis of the micropore structure of activated carbons focusing on optimum CO2 adsorption. (June 2022) - Kwiatkowski, Mirosław; Kalderis, Dimitrios; Tono, Wataru; Tsubota, Toshiki
Abstract: In this work, the porous structure of activated carbons prepared from Moso bamboo were mathematically analysed. At first, the raw material was subjected to two-stage activation process i.e. in the first stage, phosphoric acid or zinc chloride was used followed by second stage physical activation or chemical activation with potassium hydroxide. Then, nitrogen and carbon dioxide adsorption isotherms were determined. Subsequently, a novel, clustering-based adsorption analysis method was applied, combined with a numerical procedure for the fast multivariant identification of adsorption systems. The mentioned method takes into consideration the heterogeneity of the adsorbent surface and allows the determination of the adsorption energy as well as the shape and size of the clusters of adsorbate molecules formed in the pores of the analysed material. Additionally, the Quenched Solid Density Functional Theory was selected to determine the cumulative pore volume, pore size distributions and other micropore parameters. The analyses revealed a considerable degree of complexity of the carbons' porous structure, including differences in the adsorption of CO2 and N2 . The complementarity of the applied methods leads to the reliable determination of the optimum activated carbon for CO2 adsorption and assists reverse engineering approaches in the production and activation stage. Highlights: Highly porous activated carbons were produced from moso bamboo residues. Chemical activation by H3 PO4 or ZnCl2 was followed by either physical activation or chemical activation with KOH. The extensive structure of micropores was only accessible to CO2 molecules but inaccessible to N2 molecules. The carbon activated with 1:3 H3 PO4 and 1:2 KOH was the optimum for CO2 adsorption.